Особливості обліку скрапленого вуглеводневого газу під час зберігання та транспортування - Зівенко, О. В.; Zivenko, Oleksiy (Видавництво Львівської політехніки, 2019)
Щоб запобігти ухилянню від сплати акцизного податку під час зберігання та транспортування скраплених вуглеводневих газів (СВГ), для суб’єктів господарювання передбачено обов’язкове щоденне звітування про наявні об’єми продукту в резервуарах зберігання та об’єми перевантаження. Уваги потребує саме контроль об’єму СВГ як складної двофазної суміші, що суттєво змінює параметри фаз під час зберігання та транспортування. Важливим вважають питання контролю складу рідкої суміші, оскільки для приведення об’єму до стандартної температури повинні використовуватися дані про склад рідини. Наведено оцінки похибок, що можуть впливати на визначення об’єму СВГ у резервуарі, а саме: похибки градуювання резервуара, похибки визначення рівня рідкої фази в резервуарі, похибки, що виникають під час приведення об’єму до стандартних умов внаслідок розрахунку складу рідкої та парової фаз, похибки визначення температури СВГ.

Criminal activities in a country’s fuel sector adversely affect the country’s sustainable development. To prevent excise tax evasion during petroleum product storage and transportation various methods are used. The most effective methodology is the control of all supply chain and automation of such control. LPG is quite specific product for storage and transportation due to its two-phase composition that continuously changes parameters during storage and transportation. In the article, there are considered the problems of measuring LPG volume in a tank and estimation of the error‘s margins. Assessing the row of the errors that impact the volume calculation is described. They include the reservoir graduation error, the level measurement error, the temperature measuring error and have to be reduced to the standard conditions (temperature 15 °C) while computing the real quantity of LPG. Incorrect data about LPG liquid/vapor phase composition can occur if operator uses only passport data from the last consignment. Redistribution of the component composition occurs every time when the product’s temperature/pressure/quantity in the tank changes. The example of the change of the LPG phasic composition during the process of filling the tank is also considered and the related calculation errors are defined. The density calculation error, connected with volume calculation, is presented as a function of molar fraction of propane, mixture temperature and errors in composition and temperature. It’s concluded that the use of accounting in mass units and volume units should be held together regardless of the phase state and composition of the LPG.
LPG accounting specificity during its storage and transportation
Keywords: скраплений вуглеводневий газ; облік СВГ; об’єм СВГ; вимірювання рівня; рівнемір-лічильник; Liquefied petroleum gas; LPG accounting; LPG volume; Level measurement; Level measuring sensor